2020
DOI: 10.1002/ccd.29335
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic and bleeding risk after complex percutaneous coronary intervention in patients with or without high bleeding risk

Abstract: Objectives To evaluate utility of the complex percutaneous coronary intervention (PCI) criteria in real‐world practice. Background Applicability of procedural complexity criteria for risk stratification has not been adequately evaluated in real‐world practice. Methods Among 13,087 patients undergoing first PCI in the CREDO‐Kyoto registry cohort‐2, the study population consisted of 7,871 patients after excluding patients with acute myocardial infarction and those without stent implantation. Complex PCI was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The effects of CPCI in no‐CKD patients observed in our analysis were consistent with the findings of two large multicenter registries, ADAPT‐DES and CREDO‐Kyoto, in which no‐CKD patients represented about 80% and 60% of the population, respectively. In both studies, CPCI was associated with a > 70% higher risk of MI, stent thrombosis or recurrent coronary revascularization, a 20%−30% risk increase of major bleeding but not with an increased mortality 13,14 . On the other hand, in other registries including complex or noncomplex PCI, the presence of CKD was associated with a > 2‐time higher hazard of both ischemic and bleeding events as well as an increased mortality 9,10 …”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The effects of CPCI in no‐CKD patients observed in our analysis were consistent with the findings of two large multicenter registries, ADAPT‐DES and CREDO‐Kyoto, in which no‐CKD patients represented about 80% and 60% of the population, respectively. In both studies, CPCI was associated with a > 70% higher risk of MI, stent thrombosis or recurrent coronary revascularization, a 20%−30% risk increase of major bleeding but not with an increased mortality 13,14 . On the other hand, in other registries including complex or noncomplex PCI, the presence of CKD was associated with a > 2‐time higher hazard of both ischemic and bleeding events as well as an increased mortality 9,10 …”
Section: Discussionmentioning
confidence: 89%
“…CPCI represents approximately 30% of contemporary PCI 12,[26][27][28][29] and it is related with higher risk of recurrent ischemic events. 13,14,17,30 Very limited data exists regarding the prevalence and prognostic impact of CPCI in CKD patients. This information is crucial to better understand the most appropriate management, including the optimal antiplatelet treatment regimen, of this subset of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eligibility criteria across these trials have limited the inclusion of HIR patients, so the majority of enrolled patients had low or intermediate ischemic risk. In real-world clinical practice, physicians are still reluctant to choose very short DAPT durations for HIR patients, mainly due to concerns on their higher risk for atherothrombotic ischemic events 10,[40][41][42] . Indeed, we observed that patients who remained on DAPT at 1 year and 2 years, as expected, were more common among patients with HIR than in the non-HIR group.…”
Section: Fig 5 Cumulative Incidence Of Endpoint Events According To Esc/eacts-hir Criteria and Bleeding Risk Categorizationmentioning
confidence: 99%